The Relationship between Feeding Parenting and Maternal Self-Efficacy with the Incidence of Stunting in Toddlers - Ritanti, Ritanti; Evanda, Shelly (Poltekkes Kemenkes Jakarta III, 2025)
Stunting is a form of malnutrition in children under the age of five that remains a global health problem. This condition is influenced by various factors, including parenting in feeding and low maternal self-efficacy. This study aims to analyse the relationship between parenting in feeding and maternal self-efficacy with the incidence of stunting in toddlers in Kramat Jati Village, East Jakarta. This study used a quantitative design with analytic observation method and cross-sectional approach. The sample consisted of 366 mothers who had toddlers aged 12 to 59 months, with the sampling technique using Non-Probability Sampling through the Quota Sampling method. Data analysis was performed using the Chi-square test. The results showed a significant relationship between feeding parenting patterns and the incidence of stunting (p = 0.009; p < 0.05) and between maternal self-efficacy and the incidence of stunting (p = 0.007; p < 0.05). From these findings, it can be concluded that inappropriate feeding parenting and low maternal self-efficacy contribute to the incidence of stunting in toddlers. Therefore, family-based interventions are needed to improve feeding skills and strengthen mothers' self-efficacy to reduce stunting in the region.